Novel genetic variants associated with mortality after unrelated donor allogeneic hematopoietic cell transplantation. (October 2021) - Hahn, Theresa; Wang, Junke; Preus, Leah M.; Karaesmen, Ezgi; Rizvi, Abbas; Clay-Gilmour, Alyssa I.; Zhu, Qianqian; Wang, Yiwen; Yan, Li; Liu, Song; Stram, Daniel O.; Pooler, Loreall; et al.
Abstract: Background: Identification of non-human leukocyte antigen (HLA) genetic risk factors could improve survival after allogeneic blood or marrow transplant (BMT) through matching at additional loci or individualizing risk prediction. We hypothesized that non-HLA loci contributed significantly to 1-year overall survival (OS), disease related mortality (DRM) or transplant related mortality (TRM) after unrelated donor (URD)BMT. Methods: We performed a genome-wide association study (GWAS) in 2, 887 acute myeloid leukemia (AML), myelodysplastic syndrome (MDS) and acute lymphoblastic leukemia (ALL) patients and their ≥8/8 HLA-matched URDs comprising two independent cohorts treated from 2000–2011. Findings: Using meta-analyses of both cohorts, genome-wide significant associations ( p  < 5 × 10 −8 ) were identified in: recipient genomes with OS at MBNL1 (rs9990017, HR = 1.4, 95% CI 1.24–1.56, p  = 3.3 × 10 −8 ) and donor-recipient genotype mismatch with OS at LINC02774 (rs10927108, HR = 1.34, 95% CI 1.21–1.48, p  = 2.0 × 10 −8 ); donor genomes with DRM at PCNX4 (rs79076914, HR = 1.7, 95% CI 1.41–2.05, p  = 3.15 × 10 −8 ), LINC01194 (rs79498125, HR = 1.86, 95% CI 1.49–2.31, p  = 2.84 × 10 −8 ), ARID5B (rs2167710, HR = 1.5, 95% CI 1.31–1.73, p  = 6.9 × 10 −9 ) and CT49 (rs32250, HR = 1.44, 95% CI1.26–1.64, p  = 2.6 × 10 −8 ); recipient genomes at PILRB with TRM (rs141591562, HR = 2.33, 95% CI 1.74–3.12, p  = 1.26 × 10 −8 ) and donor-recipient genotype mismatch between EPGN and MTHF2DL with TRM (rs75868097, HR = 2.66, 95% CI 1.92–3.58, p  = 4.6 × 10 −9 ). Results publicly available at https://fuma.ctglab.nl/browse . Interpretation: These data provide the first evidence that non-HLA common genetic variation at novel loci with biochemical function significantly impacts 1-year URD-BMT survival. Our findings have implications for donor selection, could guide treatment strategies and provide individualized risk prediction after future validation and functional studies. Funding: This project was funded by grants from the National Institutes of Health, USA